HUBUNGAN AKUMULASI TIMBAL PADA RAMBUT MASYARAKAT PENGUMPUL LIMBAH BATUBARA DENGAN PENYAKIT HIPERTENSI - Putri, Dini Arista (JURNAL MEDIA KESEHATAN, 2015)
The water contamination in one place can affect the other places located far fromthe source of pollution. One of the rivers that are polluted is Bengkulu river. One of thecauses of pollution in Bengkulu river that is coal waste originating from coal mine companyin the upstream of the river, which is still in service until now. The coal handling treatment ascrushing, grinding, washing, drying and low temperature combustion can cause any harmfulchemical substances like lead. Lead can get into the human body through the digestive tractabsorption or through the respiratory tract (inhalation) and skin absorption. One way ofdisposal of heavy metal elements from the body is to accumulate in the hair, so the hairanalysis is a good way to estimate the content of heavy metal elements in the body anddetermine its connection with hypertension. The purpose of this study is to determine thecontent of lead in a coal waste accumulates in hair of coal waste collectors society inBengkulu river associated with hypertension. This study is an analytic observational studywith cross sectional study design. The case that will be studied is about the accumulation ofhair lead of coal waste collectors society in Bengkulu river against hypertension. The studylocation is in Bengkulu river. Sample examination was conducted by Atomic AbsorptionSpectrophotometry (AAS) analytical methods, and then performed statistical tests todetermine its connection with hypertension. The result of this study showed, from 40respondents there were 14 respondents (35%) who had hair lead levels > 12μg/g sufferedfrom hypertension and 13 respondents (32.5%) who had hair lead levels > 12μg/g but did notsuffered from hypertension, and p(0.03)< 0.05 value which indicates a significant association.Significant association between the levels of lead in the hair of coal waste collectors society inBengkulu river with hypertension